STUDY LITERATURE REVIEW: PERAN KOMUNIKASI INTERPERSONAL DAN KEPEMIMPINAN KHARISMATIK TERHADAP PENGAMBILAN KEPUTUSAN - Kanti Mustika Alanny; Theresia Anggraini; Nurma Linda Malian; Teguh Trianung; Supadi Supadi (STKIP Pesisir Selatan, 2023)
Leadership roles according to their position. When it comes to making decisions and taking responsibility for the results, leaders play a vital role. The decision shows the character of a leader. Making decisions is an important part of running an organization and a key or core part of leadership. Leaders must be able to choose the best option from a variety of alternatives in various circumstances. In order not to cause harm to the organization, the alternative that poses the smallest negative risk must be chosen. For supporting applications, leaders must be able to explain the reasons for choosing an alternative in an easy-to-understand way. This research focuses on the role of charismatic leadership and interpersonal communication in making decisions. Thus, the research method used is a literature review study by analyzing several previous research articles and writings related to the research focus. The aim of the research is to analyze and understand the impact of charismatic leadership and interpersonal communication on decision-making roles.